2014
DOI: 10.1089/tmj.2013.0097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Portal Secure Messages and Electronic Visits on Adult Primary Care Office Visits

Abstract: No significant change in face-to-face visit frequency was observed following implementation of portal messaging. Secure messaging and e-visits through a patient portal may not result in a change of adult primary care face-to-face visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 13 publications
5
73
0
Order By: Relevance
“…[1][2][3][4] The current analysis extends these observations by identifying no difference in hospitalizations or ED visits among EM users and nonusers.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…[1][2][3][4] The current analysis extends these observations by identifying no difference in hospitalizations or ED visits among EM users and nonusers.…”
Section: Discussionsupporting
confidence: 55%
“…However, studies show mixed results, with some reporting increased outpatient visits, [1][2][3] and others showing no effect. 4 Some studies reported that EM is associated with lower HbA1c levels. 2,[5][6][7][8] Thus far, studies regarding EM have not differentiated between type 1 and type 2 diabetes, examined message content, or examined the impact of EM on hospital or emergency department (ED) visits.…”
mentioning
confidence: 99%
“…Enhanced access and continuity are critical enablers of a therapeutic relationship. Practices that focus on these aspects are increasingly making communications available to patients via telephone and a web portal or e-mail, 35 and are working out mechanisms for channeling communications to appropriate staff in care teams. 36,37 The therapeutic relationship is increasingly understood to be central to health and healing and to the patient experience.…”
Section: Direct Care Activitiesmentioning
confidence: 99%
“…Others have found that patient access to health records and messaging through Internet portals was not associated with an increase in primary care utilization. 4,5 Portal tracking data make it possible to determine whether specific uses of the patient Internet portals could lead to greater health care utilization. We hypothesized that logging into the portal to view sections of the medical record regardless of whether office visit notes are viewable, and/or to message with providers about clinical issues would not lead to increased ambulatory care utilization.…”
mentioning
confidence: 99%